Understanding female and male empowerment in Burkina Faso using the project-level Women’s Empowerment in Agriculture Index (pro-WEAI): A longitudinal study - Crookston, Benjamin T.; West, Josh H.; Davis, Siena F.; Hall, P. Cougar; Seymour, Greg; Gray, Bobbi L. (Springer, 2021)
Background: Achieving gender equality and women’s empowerment is a major global priority. The purpose of this study was to determine whether the Building the Resilience of Vulnerable Communities in Burkina Faso (BRB) project, an agricultural development program, improved women’s empowerment, as measured by the project-level Women’s Empowerment in Agriculture Index (pro-WEAI). Methods: This study used a longitudinal, quasi-experimental study design. Participants included both treatment and comparison groups (total N = 751) comprising female members of savings groups and their husbands or main male household member in Burkina Faso. All participants completed the pro-WEAI questionnaire at both baseline and endline. The treatment group received a comprehensive intervention package consisting of agriculture loans and services, microenterprise loans, and education, nutrition education, and women’s empowerment programs including gender-based discussions designed to facilitate personalized changes in gender relations. Results: The proportion of the treatment group achieving empowerment did not change from baseline for women, but improved substantially for men. Women from the comparison group saw an increase in empowerment at endline while men saw a substantial decrease. Gender parity was high for women in both groups at baseline and increased slightly at endline. Women were more likely to have adequate empowerment in input in productive decisions, group membership, and membership in influential groups than men while men were more likely to have adequate empowerment in attitudes about domestic violence, control over use of income, and work balance than women. Participants from the treatment group reported an increase in the average number of empowerment indicators that they were adequate in while the comparison group saw a decrease in average adequacy over time (p = 0.002) after controlling for age, sex, and level of education. Conclusion: Despite starting at an empowerment disadvantage, the treatment group experienced gains in individual indicators of empowerment while the comparison group men and women experienced mixed results, with the women gaining, and the men losing empowerment. This research suggests that the BRB intervention may have provided some protection for the treatment group when they faced an economic down-turn prior to the endline, indicative of household resilience. Future research should consider and strengthen relationships between resilience and empowerment.